Odpowiedź :
a)
[tex]5*z+10=8*z+z+9\\5z+10=8z+z+9\\5z-8z-z=9-10\\-4z=-1\\z=\frac{1}{4}\\[/tex]
Sprawdzenie:
[tex]5*\frac{1}{4}+10=8*\frac{1}{4}+\frac{1}{4}+9\\\frac{5}{4}+10=\frac{8}{4} +\frac{1}{4}+9\\\frac{5}{4}-\frac{1}{4}=2+9-10\\\frac{4}{4}=11-10\\1=1\\[/tex]
b)
[tex]6*z-8-z=9-2*z-3\\6z-8-z=9-2z-3\\6z-z+2z=9-3+8\\7z=14\\z=2[/tex]
Sprawdzenie:
[tex]6*2-8-2=9-2*2-3\\12-8-2=9-4-3\\2=2\\[/tex]
Odpowiedź:
[tex]5z+10=8z+z+9\\\\5z+10=9z+9\\\\5z-9z=9-10\\\\-4z=-1\ \ /:(-4)\\\\z=\frac{1}{4}\\\\\\Spr.\\\\L=5\cdot\frac{1}{4}+10=\frac{5}{4}+10=\frac{5}{4}+\frac{40}{4}=\frac{45}{4}=11\frac{1}{4}\\\\P=9\cdot\frac{1}{4}+9=\frac{9}{4}+9=\frac{9}{4}+\frac{36}{4}=\frac{45}{4}=11\frac{1}{4}\\\\L=P[/tex]
[tex]6z-8-z=9-2z-3\\\\5z-8=6-2z\\\\5z+2z=6+8\\\\7z=14\ \ /:7\\\\z=2\\\\\\Spr.\\\\L=5\cdot2-8=10-8=2\\\\P=6-2\cdot2=6-4=2\\\\L=P[/tex]